Distinct permeation profiles of the connexin 30 and 43 hemichannels. Issue 8 (3rd February 2014) - Hansen, Daniel Bloch; Braunstein, Thomas Hartig; Nielsen, Morten Schak; MacAulay, Nanna
Abstract : Connexin 43 (Cx43) hemichannels may form open channels in the plasma membrane when exposed to specific stimuli, e.g. reduced extracellular concentration of divalent cations, and allow passage of fluorescent molecules and presumably a range of smaller physiologically relevant molecules. However, the permeability profile of Cx43 hemichannels remains unresolved. Exposure of Cx43‐expressing Xenopus laevis oocytes to divalent cation free solution induced a gadolinium‐sensitive uptake of the fluorescent dye ethidium. In spite thereof, a range of biological molecules smaller than ethidium, such as glutamate, lactate, and glucose, did not permeate the pore whereas ATP did. In contrast, permeability of glutamate, glucose and ATP was observed in oocytes expressing Cx30. Exposure to divalent cation free solutions induced a robust membrane conductance in Cx30‐expressing oocytes but none in Cx43‐expressing oocytes. C‐terminally truncated Cx43 (M257) displayed increased dye uptake and, unlike wild type Cx43 channels, conducted current. Neither Cx30 nor Cx43 acted as water channels in their hemichannel configuration. Our results demonstrate that connexin hemichannels have isoform‐specific permeability profiles and that dye uptake cannot be equaled to permeability of smaller physiologically relevant molecules in given settings.